2008
DOI: 10.1128/aem.00573-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of the Effect of Cationic Biocides on Bacterial Population Dynamics and Susceptibility

Abstract: Cationic biocides (CBs) are widely used in domestic and public hygiene and to control biofouling and microbial contamination in industry. The increased use of biocides has led to concern regarding possible reductions in biocide effectiveness. Domestic drain microcosms were stabilized for 5 months and then exposed to polyhexamethylene biguanide (PHMB) at 0.1, 0.2, and 0.4g liter ؊1 over 6 months and characterized throughout by differential culture, together with eubacterial-specific PCR-denaturing gradient gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 49 publications
3
44
0
2
Order By: Relevance
“…A system previously validated to be highly selective for changes in antimicrobial susceptibility (26,27) was used. Reproducible ca.…”
Section: Bacteriamentioning
confidence: 99%
“…A system previously validated to be highly selective for changes in antimicrobial susceptibility (26,27) was used. Reproducible ca.…”
Section: Bacteriamentioning
confidence: 99%
“…Стійкість мікроорганізмів до нього також практично не формується. Якщо в окремих випадках адаптація до суббактеріостатичних концентрацій ПГМГ і можлива, то не виникає перехресна резистентність [1,14]. Зростання стійкості мікроорганізмів до ПГМГ супрово джується збільшенням чутливості до інших катіонактивних препаратів.…”
unclassified
“…We found a significant decrease in hBD-3 susceptibility for both exposure times 261 only for S. capitis 19/2 and after 3h exposure to hBD-3 for S. warneri 16/1.In three cases 262 more CHG-exposed bacteria were killed by hBD-3 compared to non-exposed bacteria, al-263 though in one case the difference was less than 0.4 log-scales (Figures 1-5). Exposure to CH has been reported to result in adaptation, e.g., in skin bacteria [23], and 274 thus, changes susceptibility to different antibiotics and biocides [15][16][17][18][19][20][21][22]. Therefore an influ-275 ence of previous exposure to CHG on susceptibility to hBD-3 is possible due to the structural 276 properties of both substances and their comparable mode of action.…”
mentioning
confidence: 99%
“…48 49 It has been reported that different bacterial species are able to adapt to sub-lethal concentra-50 tions of CH [15][16][17][18][19][20] and that this adaptation affects the susceptibility to different biocides [21] 51 and antibiotics in Pseudomonas stutzeri [16,21,22]. Moore et al showed that different skin 52 bacteria were able to adapt to CH after repeated exposure [23]. 53 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Reichel et al Bacterial response to human β-Defensin-3 after chlorhexidine exposure 5 To the best of our knowledge, there are no studies on whether CHG exposure changes the 55 response of Gram-positive bacteria to antimicrobial peptides, such as hBD-3.…”
mentioning
confidence: 99%